A fragilidade da limitação da responsabilidade civil frente ao instituto da desconsideração da personalidade jurídica - Salem, Thomas (2022)
The present monograph has as its object the study of the legal institute of the disregard of legal entity, addressing its concept, origin, modalities and application procedures, as well as its relationship with the principle of patrimonial autonomy and the limitation of civil liability in the corporate environment, verifying whether there is an antagonistic nature or not between such institutes. Additionally, the present work seeks to verify whether the manner in which the disregard of legal personality was incorporated into the Brazilian legal system, and the manner in which it is applied, has resulted in a weakening and diminution of the principle of patrimonial autonomy. The purpose of this monograph is to contribute to Brazilian academic research on corporate law, specifically in the niche of the disregard of legal entity, a legal matter with relevant socioeconomic impacts, which was born in the United States of America and in Europe, especially in England, Germany and Italy. Finally, the completion of the monograph is a mandatory requirement for the conclusion of the law course at the Law School of the Pontifical Catholic University of São Paulo, since the present production is mandatory for graduation and bachelor's degree